(untitled) (مجلة العلوم الإنسانية والتطبيقية, 2017)
In this paper we introduce new subclasses of starlike functions in the open unit disk by using fractional derivative operator. We obtain coefficient inequalities and distortion theorems for functions belonging to these subclasses. Further results include distortion theorems (involving the generalized fractional derivative operator). The radii of convexity for functions belonging to these subclasses are also studied.